Histopathological evaluation of skin wound in rabbits treated by systemic dexamethasone - Kashmola, Muhanad Ali Hamdon; Mustafa, Nazih Shaban; Mustafa Al-Ahmad, Basma Ezzat; Al-Ani, Imad Matloub Dally (2011)
Background: Healing of all damaged tissues including skin wounds have an identical pattern and depends on numerous intrinsic and extrinsic factors, one of these factors is cortisone hormone.